2008
DOI: 10.1164/rccm.200708-1251oc
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Therapy against CCR3 and the Common Beta Chain Attenuates Allergen-induced Eosinophilic Responses

Abstract: TPI ASM8 attenuates the allergen-induced increase in target gene mRNA and airway responses in subjects with mild asthma. Clinical trial registered with www.clinicaltrials.gov (NCT 00264966).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 26 publications
2
83
1
Order By: Relevance
“…The phase 2a studies that have been performed until now have not shown any of this potential toxicity but longer term studies are needed to confirm these results. Furthermore, to date AON have been delivered via inhalation of a nebulisate to asthma patients (Gauvreau et al 2008;Gauvreau 2010), but not to COPD patients who have severely decreased FEV 1 . How well this patient cohort inhales the nebulisate would need to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase 2a studies that have been performed until now have not shown any of this potential toxicity but longer term studies are needed to confirm these results. Furthermore, to date AON have been delivered via inhalation of a nebulisate to asthma patients (Gauvreau et al 2008;Gauvreau 2010), but not to COPD patients who have severely decreased FEV 1 . How well this patient cohort inhales the nebulisate would need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An initial Phase 2 study design does not test in COPD patients but rather in allergic asthmatic patients following inhaled allergen challenge (2009). Another AON drug, ASM8 designed specifically for asthma and as such has targets different from PXS TPI1100, has demonstrated clinical efficacy in this allergen challenge model (Gauvreau et al 2008;Gauvreau 2010) clearly showing the potential for the AON approach. An advantage of this allergen challenge model is that the studies are generally brief in duration and the fall in FEV 1 is a well-recognized response as well as the incorporation of monitoring induced sputum allows for other inflammatory indicators to be measured.…”
Section: Challenges In Copd Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This general concept can be harnessed experimentally and therapeutically by the delivery of anti-sense RNAs. Human trials are underway to regulate protein and gene expression to modify diseases such as leukemia, Duchenne Muscular Dystrophy, and inflammatory conditions [3][4][5] . Among the challenges with RNA therapies is the relatively unstable nature of RNAs.…”
Section: Bodymentioning
confidence: 99%
“…The antisense oligonucleotide TPI ASM8 targeted against CCR3 had some effect in reducing sputum eosinophils and airway inflammation in response to allergen provocation in patients with mild atopic asthma. However, TPI ASM8 also contains an antisense oligonucleotide against the common b-chain of the receptors for IL-3, IL-5 and granulocyte-macrophage colony-stimulating factor, making the results difficult to interpret in terms of a specific effect on CCR3 antagonism [23]. However, TPI ASM8 may prove to be more effective if tested using larger patient numbers with more severe allergic asthma who exhibit a sputum eosinophilia associated with disease exacerbation; an approach that might validate targeting more than one asthma-relevant cytokine/chemokine.…”
Section: Eotaxinmentioning
confidence: 99%